An Efficient One-Pot Multicomponent Synthesis of 4-Aza-Podophyllotoxin Derivatives in Ionic Liquid. (24th October 2013) - Naeimi, Hossein; Rashid, Zahra; Zarnani, Amir Hassan; Ghahremanzadeh, Ramin
Abstract : A simple, green, and efficient procedure for the synthesis of 4-aza-podophyllotoxin derivatives by using a one-pot three-component reaction of benzaldehydes, 1, 3-cyclohexanediones, and anilinolactones in the presence of catalytic amount of alum in 1-butyl-3-methylimidazolium triflate as green media is described. This reaction proceeded under mild conditions with the use of an inexpensive and readily available catalyst, high to excellent yields, and simple workup procedure.